The boys [large type] : a memoir of Hollywood and family - Howard, Ron, 1954-; Howard, Clint, 1959- (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
By turns confessional, nostalgic, heartwarming and harrowing, the award-winning filmmaker and his brother, an audience-favorite actor, share their unusual family story of navigating and surviving life as sibling child actors.